Multifocal Intradural Extramedullary Pilocytic Astrocytomas of the Spinal Cord: A Case Report and Review of the Literature. Issue 2 (15th December 2016) - Basheer, Azam; Rammo, Richard; Kalkanis, Steven; Felicella, Michelle M.; Chedid, Mokbel
Abstract: BACKGROUND AND IMPORTANCE: Pilocytic astrocytoma (PA) is among the most common of the central nervous system gliomas in the pediatric population; however, it is uncommon in adults. PAs of the spinal cord in adults are even rarer, with only a few cases found in the literature. We report here the first case in the literature of multifocal intradural extramedullary spinal cord PAs in an adult. CLINICAL PRESENTATION: Our patient is a 56-yr-old female who presented with loss of balance and an ataxic gait. Multiple extramedullary spinal cord tumors were identified intraoperatively, the lesions completely resected, and all diagnosed as PAs. CONCLUSION: This case illustrates a unique instance of multifocal intradural extramedullary spinal cord PAs in an adult with no previous history of PA during childhood, no known familial syndromes, and no brain involvement.